2016
DOI: 10.5826/dpc.0603a05
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy could be useful in differentiating sarcoidosis from necrobiotic granulomas even after treatment with systemic steroids

Abstract: Background:Diagnosing cutaneous sarcoidosis and necrobiotic granulomas is challenging.Objective:Assessing the value of dermoscopy in differentiating cutaneous sarcoidosis from necrobiotic granulomas and evaluating whether their dermoscopic features will be altered after treatment.Methods:Nineteen cutaneous sarcoidosis and 11 necrobiotic granuloma patients (2 necrobiosis lipoidica, 4 granuloma annulare and 5 rheumatoid nodule) were included in this study. The diagnosis was confirmed by skin biopsy. The lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
3
27
0
1
Order By: Relevance
“…Such a variability is easily explained by the fact that the visibility of the vessels, especially if they are faint (as in GA), is highly affected by the type of dermoscopic techniques employed (better visualization with polarized devices) and the amount of pressure applied to the skin during the examination [3,7] . Regarding whitish areas, our results are in line with what was observed in other analyses, in which they turned out to be the most frequent non-vascular feature, with a prevalence ranging from 63.8 to 100.0% [20,21,24] . Such a finding is probably the result of the common occurrence of collagen degeneration/mucin deposition in GA, which may be responsible for whitish discolouration on dermoscopic examination [3,7,23] .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Such a variability is easily explained by the fact that the visibility of the vessels, especially if they are faint (as in GA), is highly affected by the type of dermoscopic techniques employed (better visualization with polarized devices) and the amount of pressure applied to the skin during the examination [3,7] . Regarding whitish areas, our results are in line with what was observed in other analyses, in which they turned out to be the most frequent non-vascular feature, with a prevalence ranging from 63.8 to 100.0% [20,21,24] . Such a finding is probably the result of the common occurrence of collagen degeneration/mucin deposition in GA, which may be responsible for whitish discolouration on dermoscopic examination [3,7,23] .…”
Section: Discussionsupporting
confidence: 81%
“…Moving to the usefulness of dermoscopy in the differential diagnosis of GA, several studies have emphasized that such a technique may be helpful to distinguish this dermatosis from both sarcoidosis and necrobiosis lipoidica, based on the assumption that yellowish/orangish colour and focussed vessels, typical of the latter conditions, are rarely seen in GA [20,21,24] . However, while a similar rule could be still considered for lesions showing an interstitial histological pattern, our analysis revealed that classic GA having a palisading granuloma histology may commonly display yellowish/orangish structureless areas, so only a meticulous assessment of vascular structures might orientate towards a correct diagnosis, with blurry vessels being indicative of GA and focused vessels being characteristic of sarcoidosis (linear or branching vessels) and necrobiosis lipoidica (commashaped, network-shaped/hairpin-like, or elongated, branching and focussed serpentine vessels) [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Routine follow-up is going on as relapse rate is very high in sarcoidosis. 7,8,9 Depending on the available data, the relapse rate of sarcoidosis varies from 13%-75%. In our study, no relapse case reported till date in fortunately.…”
Section: Histopathological Examinationmentioning
confidence: 99%